Агрегация оценок экспертов при принятии групповых решений - Колпакова, Т. А. (Видавництво Львівської політехніки, 2011)
The problem of taking into account opinion of several experts in making group decisions is considered. A method for calculating the total score and the coefficient of confidence in the expert's opinion in the survey is suggested.
Keywords: принятие групповых решений; экспертная комиссия; метод анализа иерархий; компетентность эксперта